Indonesian General Elections in the Perspective of Pancasila - Sukino Sukino (Green Social: International Journal of Law and Civil Affairs, 2025)
The highest sovereignty lies in the hands of the people and is carried out based on the Constitution". Likewise, Article 1 paragraph (3) which reads: "The State of Indonesia is a State of Law". Previously known as a state based on law (rechtsstaat). This concept is an elaboration of the Rule of Law concept, guided by the continental European legal system. From the perspective of understanding people's sovereignty, the highest sovereignty lies in the hands of the people. The highest power in the hands of the people is limited by the agreement that they themselves determine together which is stated in the rules of law which culminates in the formulation of the constitution as a product of the highest agreement of all the people. The democratic system as stated in Article 1 Paragraph (2) of the 1945 Constitution of the Republic of Indonesia, that: "is marked by direct democracy by the people, from the people, and for the people". So the head of state who before the amendment was elected by the MPR RI has changed where he is elected directly by the people through the election of the president and vice president and even regional heads (regional elections). Government for the people means that the power given from and by the people to the government must be exercised for the benefit of the people.Therefore, there needs to be government sensitivity to the needs of the people and to the aspirations of the people which need to be accommodated and then followed up through the issuance of policies or through the implementation of government work programs. This paper uses normative legal research conducted with a statutory and conceptual regulatory approach which will later assess the Indonesian General Election in the Pancasila.